A Study on Statistical Convergence of Sequences: Exploring Total Function and Statistical Convergence in Sequence Spaces (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Studies on sequence spaces were additionally reached out through Sum capacity Theory. The entirety capacity hypothesis began from the endeavors made by the mathematicians as far as possible to the disparate sequences, on taking its change. O. Latrines were the main individual to consider the aggregate capacity strategies as a class of changes of complex sequences by complex interminable networks. It was trailed by the works because of I. Schur, S. Mazur, W. Orlicz, K'Knopp, G. M. Petersen, S. Banach, G. Kothe and 0. Toeplitz, are a couple to be named. The takes a shot at paranormed sequence spaces was started by H. Nakano and S. Simons. It was additionally concentrated by 1. J. Maddox, C. G. Lascarides, S. Nanda, D. Rath , G. Das , Z.U.Ahmed, B. Kuttner and numerous others.